Systematic analysis of Intelligent retail system structure and its optimization - Du, Qiyang (Transactions on Computer Science and Intelligent Systems Research, 2024)
The article delves into the transformative realm of Smart Retail, exploring its evolution, technological foundations, and real-world applications. With a focus on cutting-edge technologies such as Smart Shelf Systems, Radio Frequency Identification (RFID) Tags, Near Field Communication (NFC) Technology, Smart Carts, and advanced algorithms like eXtreme Gradient Boosting (XGBoost) and Asynchronous Advantage Actor-Critic (A3C), this paper offers a comprehensive analysis of the role of these technologies in reshaping the retail landscape. The document presents in-depth discussions on the principles, working mechanisms, and operational processes of these Smart Retail components, drawing insights from case studies such as Xingbianli, Metro, and Wumart Group. Furthermore, the study explores the integration of IoT, data analytics, and artificial intelligence in retail operations, highlighting the potential for enhanced customer experiences, operational efficiency, and market competitiveness. The conclusion emphasizes the significance of Smart Retail in driving innovation, improving decision-making, and meeting the evolving demands of modern consumers. This research provides valuable insights for retailers, technology developers, and industry stakeholders seeking to navigate the dynamic landscape of Smart Retail and harness its transformative potential.